1977
DOI: 10.1139/f77-045
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Interpreting Data Obtained by Diel Sampling of Fish Stomachs

Abstract: A simple differential equation model describing the level of food in the stomach, incorporating simultaneous ingestion and gastric evacuation, is used to gauge the sensitivity of methods that utilize diel change in food level of the stomach to determine diel feeding activity of fish. Analysis of model behavior under different feeding regimes shows that diel pattern of food level in the stomach is less sensitive to feeding regime than many authors claim.An expression is derived for the magnitude of bias associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
192
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 0 publications
1
192
0
7
Order By: Relevance
“…Daily ration values were calculated using summarized prey energy per fish and the gastric evacuation rate. The total energy observed in a stomach sample was multiplied by the brook trout gastric evacuation rate (based on temperature; Sweka et al 2004) and divided by fish weight to calculate an observed consumption value (J.g fish wet weightC1.h-I) as suggested by Eggers (1977). This estimate was multiplied by 24 to convert it to a daily ration.…”
Section: Methodsmentioning
confidence: 99%
“…Daily ration values were calculated using summarized prey energy per fish and the gastric evacuation rate. The total energy observed in a stomach sample was multiplied by the brook trout gastric evacuation rate (based on temperature; Sweka et al 2004) and divided by fish weight to calculate an observed consumption value (J.g fish wet weightC1.h-I) as suggested by Eggers (1977). This estimate was multiplied by 24 to convert it to a daily ration.…”
Section: Methodsmentioning
confidence: 99%
“…Ceci a pour conséquence de réduire la croissance, la condition et la survie des prédateurs (Stewart et al 1981;Kitchell et Crowder 1986;Stewart et Ibarra 1991;Rand et Stewart 1998). Cette situation provoque, par la suite, le phénomène inverse où une faible abondance de prédateurs permet aux proies de recouvrer des niveaux d'abondance plus élevés (Rand et al 1994 Les résultats obtenus, suite à l'estimation de la consommation, à l'aide de la méthode d 'Eggers (1977) suggèrent que le modèle bioénergétique de la ouananiche surestime la consommation. En effet, la consommation prédite par le modèle est de deux à sept fois supérieure à celle observée avec la méthode d 'Eggers (1977).…”
Section: Analyse De Sensibilitéunclassified
“…Cette situation provoque, par la suite, le phénomène inverse où une faible abondance de prédateurs permet aux proies de recouvrer des niveaux d'abondance plus élevés (Rand et al 1994 Les résultats obtenus, suite à l'estimation de la consommation, à l'aide de la méthode d 'Eggers (1977) suggèrent que le modèle bioénergétique de la ouananiche surestime la consommation. En effet, la consommation prédite par le modèle est de deux à sept fois supérieure à celle observée avec la méthode d 'Eggers (1977). Nous avons utilisé la méthode d'Eggers d'une façon non conforme.…”
Section: Analyse De Sensibilitéunclassified
See 2 more Smart Citations